Study on the breakdown characteristics of the trigatron spark gap triggered by plasma jet - Li Chen; Hao Fan; Ruifeng Cao; Weihong Yang; Ying Li (AIP Advances, 2020)
The breakdown characteristics of a trigatron spark gap triggered by a plasma jet are studied in this paper; the development of a plasma jet and the influence of the gap distance, working coefficient, and plasma jet ejection properties on breakdown characteristics are compared. The results show that the plasma jet ejecting process can be divided into expanding, steady, and dissipating phases. The electric field distortion induced by the plasma jet is different during the expanding and dissipating phase, in which the plasma jet length increases and the radius of the curvature of the plasma jet front decreases, respectively. As the two processes have different variation rates, a faster increasing rate of the breakdown delay can be obtained during the dissipating phase. A detailed physical mode that explains the effects on the triggered breakdown process is presented. The shape of a plasma jet induced by polyethylene and ceramic surface discharge changes to a great extent during the dissipating phase; a more stable plasma jet can be obtained when induced only by polyethylene, resulting in a smaller breakdown delay under a low working coefficient. The ultraviolet radiation (UV) generated by the plasma jet is effective in reducing the critical breakdown electric field, while the electric field distortion induced by the plasma jet is the main reason behind the triggered breakdown under different working coefficients; the UV could play a limited role in the triggered breakdown process.